PEMROSESAN GAMBAR 360° UNTUK APLIKASI SURVEILLANCE SISTEM KENDARAAN LISTRIK OTONOM - Manullang, Yan Ario Eko Panca; Satyawan, Arief Suryadi; Siswanti, Ike Yuni (Akademi Angkatan Udara, 2022)
Surveillance serves to monitor the security of a camera-based area, therefore, the need for technology in the 4.0 era where technology is growing and increasingly sophisticated. Currently the development and availability of surveillance cameras with the need to cover a wider area, the need for clarity on the aspect of supervision is therefore made developments based on conventional cameras as 360° cameras. Some of the external factors that are difficult to avoid based on 360° cameras are distortion of the image and where this distortion refers to geometric distortion. Can cause the layout of the captured image information 360° camera distortion causes disinformation, there needs to be a solution based on these geometric deviations. In conclusion, after the Matlab program is run and works well using 360° image processing software using the Matlab programming language and the information can also be conveyed very clearly without reducing the function of the image based on the initial image. The suggestion is that every 360° image processing into a cube grayscale form and the marcator can be developed into realtime form, so that it can be applied directly to autonomous electric vehicles.